Methionine restriction affects oxidative stress and glutathione-related redox pathways in the rat. (April 2013) - Maddineni, Sreenivasa; Nichenametla, Sailendra; Sinha, Raghu; Wilson, Ronald P; Richie, John P
Lifelong dietary methionine restriction (MR) is associated with increased longevity and decreased incidence of age-related disorders and diseases in rats and mice. A reduction in the levels of oxidative stress may be a contributing mechanistic factor for the beneficial effects of MR. To examine this, we determined the effects of an 80% dietary restriction of Met on different biomarkers of oxidative stress and antioxidant pathways in blood, liver, kidney and brain in the rat. Male F-344 rats were fed control (0.86% methionine) or MR (0.17% methionine) diets for up to six months. Blood and tissues were analyzed for glutathione (GSH) concentrations, related enzyme activities and biomarkers of oxidative stress. MR was associated with reductions in oxidative stress biomarkers including plasma 8-hydoxydeoxyguanosine (8-OHdG) and 8-isoprostane and erythrocyte protein-bound glutathione after one month with levels remaining low for at least six months ( P < 0.05). Levels of free GSH in blood were increased after 1–6 months of MR feeding whereas liver GSH levels were reduced over this time ( P < 0.05). In MR rats, GSH peroxidase activity was decreased in liver and increased in kidney compared with controls. No changes in the activities of GSH reductase in liver and kidney and superoxide dismutase in liver were observed as a result of MR feeding. Altogether, these findings indicate that oxidative stress is reduced by MR feeding in rats, but this effect cannot be explained by changes in the activity of antioxidant enzymes.